CHANGE OF VOCALISMS IN PERSIAN-TAJIK BORROWINGS (Scientific journal of the Fergana State University, 2023)
This article discusses language vocabulary, lexical richness of a language, the transition of lexical units from one language into another, the phonetic phenomena  that  occur in the borrowings of Uzbek  language, the combinatory and positional changes of  sounds in speech and vocalisms in Persian-Tajik dialects